Criterion A and Non-Criterion A Racial Discrimination Experiences, Posttraumatic Stress Symptoms, and Posttraumatic Cognitions Among Black or African Americans - Wamser, Rachel Ann (Journal of interpersonal violence, 2024)
Racial discrimination is an unfortunately common experience for Black Americans with detrimental physical and mental health consequences. Prior research has established an association between discrimination and posttraumatic stress symptoms (PTSS); yet, trauma-related cognitions have not been studied. The majority of the existing empirical work in this area has not examined specific forms of discrimination experiences, despite potential key differences in these adversities. Relatedly, some forms of discrimination constitute “traumatic” events as defined by Criterion A for PTSD in the DSM-5 while others do not, and these distinctions have also been overlooked. Thus, the present study aimed to (a) examine discrimination, including specific types, in relation to PTSS and posttraumatic cognitions and (b) investigate whether Criterion A and non-Criterion A discrimination experiences were tied to PTSS and trauma-related thoughts. Participants were 172 undergraduate students who identified as Black or African American (Mage = 25.11, SD = 8.25, range = 18–56; 84.9% female). Results indicated that while cumulative trauma was unrelated to PTSS, discrimination experiences were linked with higher PTSS and negative posttraumatic cognitions. Specifically, avoidance discrimination experiences were associated with both outcomes. Criterion A discrimination events were not tied to PTSS. These findings support previous research showing a link between racial discrimination and trauma-related outcomes. In addition, the results suggest that avoidance discrimination, while not classified as “traumatic,” may have an important contribution to PTSS and posttraumatic cognitions among Black individuals. The study underscores the need to address racial discrimination experiences, including microaggressions, within a traumatic stress context.